PENGARUH POLA ASUH OTORITER TERHADAP KECENDERUNGAN CYBERBULLYING YANG DIMEDIASI OLEH KECERDASAN EMOSIONAL (EMOTIONAL INTELLIGENCE) PADA REMAJA DI KOTA BANDUNG. - Nurlaily, Talia Hanafiah; Maslihah, Sri; Wulandari, Anastasia (Universitas Paramadina, 2020)
This study aims to determine the effect of authoritarian foster pattern on cyberbullying tendencies mediated by emotional intelligence in teenagers in the city of Bandung. This research used a quantitive approach with regression analysis methods with variable mediation method. The sample in this study were 341 teenagers lived in Bandung. The sampling technique in this study used non-probability sampling. The authoritarian foster pattern is measured using instruments according to Riberio (2009) which is the result of the adaptation of Cahyanuari (2018), emotional intelligence is measured using instruments according to Goleman (2016) which is the result of the adaptation of Jonta (2018), and cyberbullying is measured using instruments from Willard (2017) which is a result adaptation of Agustin. The data analysis technique used in this study was a simple regression analysis to determine the influence of authoritarian foster patterns against cyberbullying tendencies mediated by emotional intelligence. The results of this study show that emotional intelligence cannot be mediated on an authoritarian foster pattern against cyberbullying tendencies.